2003
DOI: 10.1002/app.11919
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maleated polypropylene on mechanical properties of composite made of viscose fiber and polypropylene

Abstract: ABSTRACT:The purpose of this work was to study how viscose fiber behaves in polypropylene (PP) matrix when maleated polypropylene (MAPP) is used as a coupling agent. The influences of processing conditions on composite properties was of interest. Composites were characterized by FTIR and mechanical testing. The most notable result was the effect of the MAPP concentration on the tensile strength of the composites; the tensile strength increased from 40 to 69 MPa when MAPP was added in amounts up to 6 wt % of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 10 publications
3
31
0
Order By: Relevance
“…This result is ascribed to the beneficial effect of MA grafting to the PP backbone, which leads to an increase of the interfacial modulus. [27][28][29][30][31][32] The interfacial modulus corresponds to the polymer modulus in the filler-matrix interphase. Figure 5b shows the evolution of the tensile strength as a function of OFI cladode flour content.…”
Section: High Strain Behavior (Non Linear Conditions)mentioning
confidence: 99%
“…This result is ascribed to the beneficial effect of MA grafting to the PP backbone, which leads to an increase of the interfacial modulus. [27][28][29][30][31][32] The interfacial modulus corresponds to the polymer modulus in the filler-matrix interphase. Figure 5b shows the evolution of the tensile strength as a function of OFI cladode flour content.…”
Section: High Strain Behavior (Non Linear Conditions)mentioning
confidence: 99%
“…[2][3][4][5][6] Small amounts of coupling agent can bring about a significant improvement of the mechanical properties of natural fiber reinforced composites. [7] Bledzki and Faruk [6] reported that 5 wt.-% maleated poly(propylene) in 50 wt.-% wood fiber-filled poly(propylene) led to 65 and 50% increase of…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Isotactic poly(propylene) (iPP) is commonly used as a matrix in wood flour based composites as it can be obtained inexpensively and is easily manufactured. [4,5] However, the problem is that the combination of the wood flour with an iPP matrix often leads to the composites having poor mechanical properties, especially tensile, impact strength and elongation at break. This can be Summary: This paper presents the results of an experimental investigation concerning the use of an ethylene butyl acrylate and glycidyl methacrylate (EBAGMA) terpolymer as an interfacial agent for isotactic poly(propylene)/wood flour (iPP/WF) composites at various filler ratios (10, 20 and 30 wt.-%).…”
Section: Introductionmentioning
confidence: 99%